The Bones of Children With Obesity - Fintini, Danilo; Cianfarani, Stefano; Cofini, Marta; Andreoletti, Angela; Ubertini, Grazia Maria; Cappa, Marco; Manco, Melania (Frontiers in Endocrinology, 2020)
Excess adiposity in childhood may affect bone development, ultimately leading to bone frailty. Previous reports showing an increased rate of extremity fractures in children with obesity support this fear. On the other hand, there is also evidence suggesting that bone mineral content is higher in obese children than in normal weight peers. Both adipocytes and osteoblasts derive from multipotent mesenchymal stem cells (MSCs) and obesity drives the differentiation of MSCs toward adipocytes at the expense of osteoblast differentiation. Furthermore, adipocytes in bone marrow microenvironment release a number of proinflammatory and immunomodulatory molecules that up-regulate formation and activation of osteoclasts, thus favoring bone frailty. On the other hand, body adiposity represents a mechanical load, which is beneficial for bone accrual. In this frame, bone quality and structure result from the balance of inflammatory and mechanical stimuli. Diet, physical activity and the hormonal milieu at puberty play a pivotal role on this balance. In this review, we will address the question whether the bone of obese children and adolescents is unhealthy in comparison with normal-weight peers and discuss mechanisms underlying the differences in bone quality and structure. We anticipate that many biases and confounders affect the clinical studies conducted so far and preclude us from achieving robust conclusions. Sample-size, lack of adequate controls, heterogeneity of study designs are the major drawbacks of the existing reports. Due to the increased body size of children with obesity, dual energy absorptiometry might overestimate bone mineral density in these individuals. Magnetic resonance imaging, peripheral quantitative CT (pQCT) scanning and high-resolution pQCT are promising techniques for the accurate estimate of bone mineral content in obese children. Moreover, no longitudinal study on the risk of incident osteoporosis in early adulthood of children and adolescents with obesity is available. Finally, we will address emerging dietary issues (i.e. the likely benefits for the bone health of polyunsaturated fatty acids and polyphenols) since an healthy diet (i.e. the Mediterranean diet) with balanced intake of certain nutrients associated with physical activity remain the cornerstones for achieving an adequate bone accrual in young individuals regardless of their adiposity degree.